1997
DOI: 10.1021/ic961364o
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Coordination Equilibria on DOTA Complexes of Lanthanide Metal Ions in Aqueous Solution Studied by 1H-NMR Spectroscopy

Abstract: A variable-temperature, -pressure, and -ionic strength 1 H NMR study of the DOTA complexes of different trivalent cations (Sc, Y, La, Ce f Lu) (DOTA ) 1,4,7,10-tetraaza-1,4,7,10-tetrakis(carboxymethyl)cyclododecane) yielded data that are in contradiction with the hitherto used model of only two enantiomeric pairs of diastereoisomers that differ in the ligand conformations. A two-isomer equilibrium cannot explain the newly observed apparent reversal of the isomer ratio at the end of the series. As both conforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
479
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 356 publications
(534 citation statements)
references
References 32 publications
40
479
1
2
Order By: Relevance
“…After many studies, it was concluded that the isomer displaying larger shifts corresponds to a nine-coordinate capped (by a coordinated water molecule) CSAP structure M, while the isomer displaying smaller shifts is either a nine-coordinate inverted CSAP m (from La to Ho), or an eightcoordinate inverted SAP m? structure (Er to Lu) [33]. In addition to the frequency difference, the two isomers also differ in population.…”
Section: Resultsmentioning
confidence: 99%
“…After many studies, it was concluded that the isomer displaying larger shifts corresponds to a nine-coordinate capped (by a coordinated water molecule) CSAP structure M, while the isomer displaying smaller shifts is either a nine-coordinate inverted CSAP m (from La to Ho), or an eightcoordinate inverted SAP m? structure (Er to Lu) [33]. In addition to the frequency difference, the two isomers also differ in population.…”
Section: Resultsmentioning
confidence: 99%
“…In all snapshots the DOTA ligand is in its major (M) conformation with approximate square antiprismatic geometry. [21,81] The major parameter influencing the 17 O hyperfine coupling constant, A iso , is the gadolinium-oxygen distance, r Gd-O , which varies during the 1-ns simulation from 2.44 to 2.7 Å (Figure 11, left). [21] The averaged A iso ( 17 O) is 0.58Ϯ0.11 MHz for an average distance of 2.56 Ϯ 0.06Å, which is in excellent agreement with the value determined from chemical shift measurements (0.59 MHz [15] ).…”
Section: +mentioning
confidence: 99%
“…The lower limit of the activation energy E v was set to 6 kJ/mol. The quality of the adjustment of the spectra is almost as good as for [Gd(H 2 (Aime et al, 1997b) in order to avoid the introduction of too many parameters. Nevertheless, the agreement with the experiments is good, without any spin rotation mechanism.…”
Section: [Gd(dota)(h 2 O)] -mentioning
confidence: 99%